Role of stressful life events and personality traits on the prevalence of wish to die among French physicians - Diaz, Emmanuel; Abad-Tortosa, Diana; Ghezal, Maha; Davin, Josephine; Lopez-Castroman, Jorge (Frontiers in Public Health, 2024)
Background Suicide rates are higher among physicians than in the general population. We aimed to investigate the role of stressful life events (related or not to work conditions) and personality traits on wish to die, a proxy measure of suicidal ideation. Methods This cross-sectional study took place in France from March 2018 to September 2018. Physicians completed an online questionnaire. A multiple logistic regression model estimated factors associated with wish to die. Moderated moderation models were used to assess the effect of personality traits on the relationship between stressful events and wish to die. Results 1,020 physicians completed the questionnaire. Most (75%) had endorsed a work-related stressful event and one in six (15.9%) endorsed a wish to die the year before. Wish to die was associated with burnout (OR = 2.65, 95%CI = 1.82–3.88) and work-related stressful events (OR = 2.18, 95%CI = 1.24–3.85) including interpersonal conflicts, harassment and work-overload. Emotional stability was the only personality trait associated with wish to die in the logistic regression (OR = 0.69, 95%CI = 0.59–0.82). In moderation models, we observed a significant interaction involving three personality traits—emotional stability, extraversion, and agreeableness—along with gender, influencing the impact of stressful events on the wish to die. Limitations Our study is limited by the impossibility to control for risk factors associated with suicide like psychiatric comorbidities. Conclusion Work-related stressful events significantly contribute to the manifestation of a wish to die among physicians. The impact of stressful events on the wish to die is moderated by factors such as gender and personality traits, including emotional stability and extraversion. These results are overall consistent with prior studies concerning the risk of burnout and suicide among physicians.